The Role Played by the Jinn in the Marriage Breakup: an Account from the Qur’an and a Hadith - Abdillah Kitota (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
All over the world, marriage breakup is a growing problem that has affected many families and societies in various ways. This study was descriptive study design that collected qualitative data from the Qur’an and six canonical books of ahadith of ahlul sunnah wal jama’ah to describe the role of the evil jinn in marriage breakup. The findings show that the evil jinn are the prevalent and hidden factor for the marriage breakup, that may either initiate or amplify the factors for the marriage breakup. The findings from this study may help Tanzanians and the world at large to avoid and overcome the effects of the evil jinn in their marriages; which include the marriage breakup. This study suggests further studies on this subject by using case study and longitudinal study designs, in order to broaden the scope of this subject.